Periodicity and environmental drivers of apical and lateral growth in a Cerrado woody species - Bosio, Fabio [UNESP]; Rossi, Sergio; Marcati, Carmen R. [UNESP] (Springer Nature, 2016)
Key message: Apical and lateral growth are seasonal in a Cerrado species, and these events are related to each other and linked with climatic and environmental features. Abstract: In the Cerrado, a tropical ecosystem with seasonal rainfall, we investigated the timing of leaf production and cambial activity, and checked whether these features are related to each other and with climatic and environmental factors. Between September 2011 and December 2012, sampling of main stem and vegetative phenological observations of Kielmeyera grandiflora (Wawra) Saddi (Calophyllaceae) were done monthly to assess seasonality in leaf production and cambial activity, and to compare these features with each other. To check the relationship of bud opening and the onset of cambial activity with climatic and environmental features, the average temperature and day length, and the precipitation sum in a time window ranging from 1 to 30 days before the occurrence of these events were recorded, and the coefficient of variation was calculated. Leaf production and cambial activity were seasonal. Bud opening occurred in September 2011 and August 2012, during the dry season. The onset of cambial activity occurred in October both in 2011 and 2012, 1–2 months after bud opening, at the beginning of the rainy season. The cambium was dormant in May, during the rainy season. Photoperiod and temperature showed low coefficients of variation in the time window before bud opening and onset of cambial activity, while rainfall presented a high coefficient of variation. Thus, both apical and lateral growth are seasonal events in Cerrado species, and are related to each other. A set of climatic and environmental features is related with seasonal growth, among which photoperiod and temperature may be important in the regulation of these events.
Keywords: Budding; Cambium; Kielmeyera grandiflora; Leaf production; Phloem; Xylem